Pancasila Sebagai Sistem Etika - Indah Jumadila Khairani; Nur Zakiah Pulungan; Monica Ayu Dia (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Ethics is a science that discusses the habits and customs that develop in society. Pancasila as an ethical system in Indonesia is closely related to the basic values contained in the five precepts of Pancasila. The purpose of Pancasila as an ethical system is to find out the reasons related to it, political sources, historical sources, and sociological sources of the ethical system in Pancasila. In addition, it can find out the dynamics or challenges and urgency and essence of Pancasila as an ethical system. The method used is a qualitative research method with a study or literature study approach. The results of this study are that Pancasila plays an important role for Indonesian citizens in regulating appropriate behavior or behavior and is a guideline and foundation for society in ethics.